2007
DOI: 10.1186/1479-5876-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Toll like receptor-3 ligand poly-ICLC promotes the efficacy of peripheral vaccinations with tumor antigen-derived peptide epitopes in murine CNS tumor models

Abstract: Background: Toll-like receptor (TLR)3 ligands serve as natural inducers of pro-inflammatory cytokines capable of promoting Type-1 adaptive immunity, and TLR3 is abundantly expressed by cells within the central nervous system (CNS). To improve the efficacy of vaccine strategies directed against CNS tumors, we evaluated whether administration of a TLR3 ligand, polyinosinicpolycytidylic (poly-IC) stabilized with poly-lysine and carboxymethylcellulose (poly-ICLC) would enhance the anti-CNS tumor effectiveness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(90 citation statements)
references
References 48 publications
1
85
0
Order By: Relevance
“…However, cancers, including gliomas, secrete numerous type-2 cytokines (3133) that promote tumor proliferation (34, 35) and immune escape (36). Our preclinical studies (5, 6) and prior phase I/II clinical study in recurrent WHO grade III/IV HGG patients (4) have indicated that poly-ICLC promotes type-1 polarization of T-cell responses against vaccine-targeted GAAs. Although limited numbers of cases were evaluated for IL-5 ELISPOT, our data further support the ability of our vaccine regimen for promoting type-1 (i.e., IFN-γ-driven) GAA-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, cancers, including gliomas, secrete numerous type-2 cytokines (3133) that promote tumor proliferation (34, 35) and immune escape (36). Our preclinical studies (5, 6) and prior phase I/II clinical study in recurrent WHO grade III/IV HGG patients (4) have indicated that poly-ICLC promotes type-1 polarization of T-cell responses against vaccine-targeted GAAs. Although limited numbers of cases were evaluated for IL-5 ELISPOT, our data further support the ability of our vaccine regimen for promoting type-1 (i.e., IFN-γ-driven) GAA-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously demonstrated that tumor-specific type-1 T cells, which predominantly secrete IFN-γ (22), but not type-2 T-cells, can efficiently traffic into brain tumor sites and mediate effective therapeutic efficacy (23) via type-1 chemokine CXCL10 (2326) and an integrin receptor VLA-4 (6, 2730). However, cancers, including gliomas, secrete numerous type-2 cytokines (3133) that promote tumor proliferation (34, 35) and immune escape (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this area of research has been devoted to the combined use of cytotoxic agents and vaccine therapy rather than to agents such as poly-ICLC. On the other hand, it does appear that poly-ICLC may improve the efficacy of anti-CNS tumor peptide-based vaccinations by augmenting the overall immune response to the vaccine [43]. Moreover, the pilot study discussed in the introduction, which used poly-ICLC in newly diagnosed or recurrent malignant gliomas did allow for concurrent use of CCNU; however, while the patients who took CCNU experienced no additional toxicities, they had similar outcomes to those who did not take it.…”
Section: Discussionmentioning
confidence: 99%
“…A well-known property of adjuvants is the enhancement of antibody responses, but genetic ablation of TLR signaling pathways did not affect the level of antibodies raised to various T-cell dependent antigens administered with a variety of classical adjuvants (Gavin et al, 2006). Likewise, administration of type I interferon or poly ICLC (a synthetic complex of polyinosinic-polycytidylic acid stabilized with poly-L-lysine and carboxymethylcellulose), a TLR-3 agonist, with attenuated PRRSV vaccination did not enhance protection against virulent challenge, and may have exacerbated disease (Charerntantanakul et al, 2006; Murtaugh and Genzow, 2011; Zhu et al, 2007). Although the molecular mechanisms by which adjuvants potentiate antigen-specific immune responses are not completely elucidated, the investigations stimulated by the discoveries of innate sentinels of danger or non-self have firmly established the role of innate responses to infection in initiation of productive antigen-specific B-cell and T-cell responses that are the foundation of vaccination.…”
Section: Innate Immune Response To Infectionmentioning
confidence: 99%